Groundwater investigation Geolistrik Methods In Regional District of Parigi Parigi Moutong - Musa, Moh. Dahlan Th (Gravitasi, 2014)
The research of groundwater investigation conducted by applying the method of geoelectric in the District Parigi Parigi Moutong. Identification of the substance of the study, conducted by survey / observations and measurements in the field.Field measurements using elektrical Vertical Sounding (VES) with Schlumberger electrode configuration. The results obtained indicate that the groundwater aquifer layer in the study area are the two lithologies are lithologies alluvium and coastal sediment and rock units molasa celebes. In the alluvium and coastal sediment units are at least 3 layers of the aquifer from surface to a depth of ± 25m bmt where perlapisannya alternating with layers aquiclude. Distribution of the aquifer layer on a flat stone units tend to follow the surface topography. In lithologies molasa celebes obtained their aquifer layer that is as aquifer (+). The upper limit of this layer is at a depth ±24.6m bmt decreases eastward at a depth ±40.2m bmt. The thickness of this layer is the average ±42m. allegedly sumurbor positive groundwater measuring point 16, 17 are located in the region kampal, 23 (Maesa), 24 (Mertasari), 30 (Bambalemo) and 35 (Maesa Coast) derived from this aquifer layer. Parigi district region is an area of discharge (discharge area), while the catchment area (recharge area) is located in the west area of research. Keywords: groundwater, geoelectric method, the method vertial Eletrrial Sounding, Schlumberger configuration